2015
DOI: 10.18632/oncotarget.v6i33
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It becomes exceedingly clear that immune cells not only use cellular metabolism to meet their bioenergetic demands, but that these metabolic pathways also determine their phenotype and function. We now also acknowledge that perturbations of distinct metabolic networks are implicated in immune cell-associated diseases. "Immunometabolism" explores the metabolic machinery in all immune subsets and studies how it regulates their immunological function in either homeostatic or pathological situations. A distinct me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Numerous studies have shown that the Wnt/β-catenin signaling pathway plays an important role in regulating HCC cell proliferation, invasion and metastasis. Cripto-1 was found to be highly expressed in about 50% of HCC tissues ( 121 ). It can bind to the FZD7/LRP6 receptor and DVL3 and stabilize the expression of DVL3.…”
Section: The Role Of the Wnt/β-catenin Signaling Pathway In The Tumor...mentioning
confidence: 99%
“…Numerous studies have shown that the Wnt/β-catenin signaling pathway plays an important role in regulating HCC cell proliferation, invasion and metastasis. Cripto-1 was found to be highly expressed in about 50% of HCC tissues ( 121 ). It can bind to the FZD7/LRP6 receptor and DVL3 and stabilize the expression of DVL3.…”
Section: The Role Of the Wnt/β-catenin Signaling Pathway In The Tumor...mentioning
confidence: 99%
“…Tumor mutational burden (TMB), as detected by tissue NGS, is a potential predictor of immunotherapy response. 101 Still, tissue biopsy of CNS tumors is invasive, making it non-ideal. A recent study published in Clinical Cancer Research confirmed that there is a correlation between high alteration number detection in ctDNA and improved response following immunotherapy; 102 supporting the use of ctDNA in place of tissue biopsy.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…LTX-315 is a synthetic 9-mer cationic oncolytic peptide developed as an analogue of bovine lactoferricin ( 5 , 6 ), which was selected from a series of chemically modified lactoferricin-derived lytic peptides because it displayed superior anticancer activity and lower toxicity on normal cells ( 5 ). LTX-315 induces tumor cell death by rapidly damaging cell membrane integrity ( 6 , 7 ) and permeabilizing mitochondrial membrane ( 8 , 9 ). Intra-tumoral administration of LTX-315 stimulates the generation of systemic tumor-specific immune responses ( 10 , 11 ), resulting in increased infiltration of cytotoxic CD8 + T cells and decreased regulatory T (Treg) cell infiltration in primary treated tumors ( 11 14 ) and in re-challenged secondary tumors ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…For tumor-infiltrating DCs (TiDCs) to traffic to dLNs for the induction of antitumor immune responses, they must mature and acquire the necessary features capable of sufficiently triggering the activation of specific T cells. Given the release of multiple damage-associated molecular patterns (DAMPs) and alarmins (ATP, HMGB1, etc) by tumor cells treated with LTX-315 in vitro ( 8 , 10 , 11 ) and the known capacities of DAMPs/alarmins to induce DC maturation ( 19 , 20 ), it has been proposed that the DAMPs/alarmins released by LTX-315-treated tumor cells are responsible for triggering the maturation of TiDCs and subsequent tumor-specific immune response ( 6 ). We therefore sought to investigate whether and how LTX-315 induces DC maturation in the context of the generation of anti-melanoma immunity.…”
Section: Introductionmentioning
confidence: 99%